2018
DOI: 10.3390/app8112101
|View full text |Cite
|
Sign up to set email alerts
|

Electrical and Mechanical Properties of Ink Printed Composite Electrodes on Plastic Substrates

Abstract: Printed flexible electrodes with conductive inks have attracted much attention in wearable electronics, flexible displays, radio-frequency identification, etc. Conventional conductive inks contain large amount of polymer which would increase the electrical resistivity of as-printed electrodes and require high sintering temperature. Here, composite electrodes without cracks were printed on polyimide substrate using binder-free silver nanoparticle based inks with zero-dimensional (activated carbon), one-dimensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…Sintering is a critical finishing step in many nanotechnological processes that can take advantage of extreme photothermal efficiency and the decrease of the melting temperature of nanomaterials . For example, the photothermal properties of plasmonic silver nanoparticles were applied for laser sintering of printed patterns at low temperatures …”
Section: Inkjet Printed Photothermally Active Patternsmentioning
confidence: 99%
“…Sintering is a critical finishing step in many nanotechnological processes that can take advantage of extreme photothermal efficiency and the decrease of the melting temperature of nanomaterials . For example, the photothermal properties of plasmonic silver nanoparticles were applied for laser sintering of printed patterns at low temperatures …”
Section: Inkjet Printed Photothermally Active Patternsmentioning
confidence: 99%
“…Some examples of their use can be found in the work of Ghosale et al [248], Park et al [249] and Kim et al [250]. Nanoparticle-based inks have impressive cyclic deformation properties, as discussed by Wang et al [251], making them suitable for flexible electronics, but care must be taken when selecting the correct nanoparticle to use in an ink. Nanoparticles such as copper nanoparticles are highly susceptible to oxidisation if they are not used with capping agents and the printing process is not carried out in an inert setting [247,252].…”
Section: Overview Of Previously Used Rfid Sensor Materialsmentioning
confidence: 99%
“…The aim is to provide solutions for the integration of diverse passive and active components on flexible (elastic) substrates for various applications from wearables to robotics, energy storage applications, bioelectronics, and functional textiles. Wang et al [44] reported the development of binder-free conductive composite inks with adjustable electrical and mechanical properties for flexible electronics applications. The developed binder-free composite inks were composed of silver nanoparticles, binary solvents, and conductive nanofillers of various architecture and composition.…”
Section: Micro/nanojoining For Microelectronicsmentioning
confidence: 99%